Entre renováveis e não renováveis: o setor de energia na agenda governamental brasileira entre 1995 e 2014 - Duarte, Cristiano Parra (2021)
This dissertation analyzes the characteristics of the Brazilian policy agenda related to the energy sector to verify the governmental priorities (longitudinally and transversally), at the federal level, between 1995 and 2014, a period that compounds both governments Fernando Henrique Cardoso and Luiz Inácio Lula da Silva, and the Dilma Rousseff’s first term. To do so, the analysis focus on the attention of the Executive (Presidency, Ministry of Mines and Energy and National Council for Energy Policy), the Legislative, and the Indirect Administration (National Electric Energy Agency, National Agency of Petroleum, Natural Gas and Biofuels and Energy Research Company). The attention of these arenas and institutions is analyzed based on presidential investiture speeches, messages to the National Congress, executive decrees, provisional measures, ministerial decrees, resolutions from the regulatory agencies and the sectorial council, technical notes from the Energy Research Company, constitutional amendments, ordinary laws, and legislative decrees. Based on the Punctuated Equilibrium Theory, created by Baumgartner and Jones, and a methodology that combines content analysis, coding processes, database construction, and statistical treatment, used and recognized internationally by the Comparative Agendas Project, this dissertation undertakes qualitative analyzes based on data content, as well as quantitative analyzes based on frequency and correlation analyses. As result, it is pointed out that the policy agenda related to the energy sector is quite diversified and that priorities fluctuate considerably over the years, delimiting periods of incremental adjustments, as well as expressive changes. It is also identified that renewable energies had attention increased in PT governments (even though non-renewable energies are among the priorities), while in Cardoso governments the priorities are turned to the electricity and oil and natural gas sectors. Furthermore, it is argued that between 1995 and 2014 the energy sector had two distinct policy images, one during the Cardoso’s governments and the other during the PT’s governments. In this perspective, the set of elements around two factors, the energy crisis during 2001-2002s and the election of Lula, changes the policy image, as well as enabling the process of diversification of the Brazilian energy matrix and the entry of renewable energies issues on the policy agenda. Finally, it is highlighted that there are important differences in the Executive, Legislative and Indirect Administration agendas and that relevant associations are noted between the priorities of Indirect Administration and the Executive. Furthermore, there is a tendency for the Executive to usually direct the National Congress's attention on the energy sector. These findings reinforce the argument that the energy sector is more insulated in the Executive and has a predominance of attention in technical and bureaucratic institutions.